PENGARUH PENDEKATAN PROSES BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI DI SEKOLAH DASAR - Nugroho, Achmad Setyo; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to analyze the effect of the application of process approach assisted media images glow against the narrative essay writing skills in Indonesian learning class III elementary schools in Pontianak Mujahidin South. The methods used to experiment with a Quasi Experimental design and non equivalent controls group design. The population of all students of 187 people. the sample of this study is the student class III D totalling 33 people as a class experiment and III E class students as class controls that add up to 31 people. Data collection techniques used are measurement techniques and data collection of assay writing his essay. Based on data analysis, the average result of post test experimental class was 78.23 and post control tests on 74.11 means. Hypothesis test results using a t-test (surveyed variance) get the count of 2,065 t = as for the level of freedom (33 + 31-2 = 62) with a significant level of α = 5% obtained t = 1,676 table, which means t calculate > t table, this proves that there are influences the application of process approach assisted media images glow against the narrative essay writing skills in indonesian learning. Based on the calculation of the effect size (ES) getting ES = 0.37 which includes secondary criteria. Keywords: Influence, Process Approach, Media Image Series, Indonesian Learning